Hacia la construcción de un fondo fiscal anticíclico - Mariano Fernández; Miriam Malament (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2023)
– The existence of incomplete financial markets, in an environment of uncertainty, is one of the problems of the Latin American economies, that determines a suboptimal path of public spending, with the consequent loss of social welfare. The existence of a high degree of positive correlation between public expenditure and revenue, condemning economies, to having credit in good times and lacking it in bad times. The objective of the work is to find a second best option through the definition of anticyclical fiscal fund that compensates for the failure of capital market, in the face of a fall in public revenue, even with loss in welfare.
Keywords: E21; E30; E60; E62; E64; G28; H21; H62; 330; Política Fiscal; Fondo Fiscal Anti cíclico; Ciclo-Tendencia; Ingresos Fiscales; Déficit y Superávit Público